Black Cutworm, Agrotis ipsilon (Hufnagel) (Insecta: Lepidoptera: Noctuidae) - John L. Capinera (EDIS)
EENY-395, a 5-page illustrated fact sheet by John L. Capinera, describes this wide-ranging pest of nearly all vegetables and many important grains. Includes selected references. Published by the UF Department on Entomology and Nematology, October 2006.